Modulation of osteogenesis and adipogenesis by human serum in human bone marrow cultures. - Oreffo, R; Virdi, A; Triffitt, J (1997)
Knowledge of the controlling mechanisms of human osteoprogenitor cell differentiation has important implications for understanding bone turnover. The in vitro differentiation of human bone marrow fibroblasts into adipogenic and osteogenic cells and the interaction of 1,25 dihydroxyvitamin D3 (1,25(OH)2D3) and dexamethasone in this process has been investigated together with the effects of human serum. Marrow fibroblasts cultured in human serum and dexamethasone for 28 days, generated lipid containing cells as confirmed by morphology, Oil red O staining and immunocytochemistry using antiserum to the adipocyte-specific protein, adipocyte P2 (aP2). In cultures containing 1,25(OH)2D3 and dexamethasone, adipogenesis was stimulated within 21 days. Osteocalcin expression, as assessed by in situ hybridization, was dependent on the presence of 1,25(OH)2D3 and was decreased in cultures treated with dexamethasone. Northern analysis confirmed the decrease in osteocalcin expression and increase in lipoprotein lipase expression with the appearance of the adipogenic phenotype in these cultures. Marrow cultures maintained for 14 days in human serum and osteotropic agents before switching to fetal calf serum indicated the continuous requirement of human serum in these cultures for adipogenesis. These results demonstrate that human serum contains factors that exert dramatic effects on human bone marrow cell differentiation to augment the osteogenic and adipogenic activity of 1,25(OH)2D3 and dexamethasone.